Ballistic Penetration Test and Simulation of Metallic Aircraft Wing Fuel Tank - Kim, Jong Heon; Seo, Bohwi; Choi, Kisub; Sung, Siyul (International journal of aeronautical and space sciences, 2023)
The development of a fighter aircraft requires reasonable assessment and validation of airframe survivability against weapon threats. Fulfilling this objective and effectively meeting the combat survivability requirements necessitates enhanced design based on simulated battle damage and organized live fire tests. The hydrodynamic ram effect occurs when a projectile penetrates the wing fuel tank of an aircraft and is the largest single source of aircraft losses. In this study, battle damage prediction and assessment of an aircraft wing fuel tank subjected to the penetration of a ballistic projectile were therefore undertaken using a two-stage live fire test and corresponding simulations. The correlation between test and simulation results was confirmed, thereby establishing techniques for testing and simulating the hydrodynamic ram effect on the aircraft sub-assembly level.